Design of Deep Learning Teaching Module in Text Learning Report Observation Results in Class VIII of State Junior High School LIK Layana Indah - Amina I.P; Juniati; Sukma; Ulfah; Fadillah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to describe the design of Deep Learning-based teaching modules  developed to support meaningful, active, and student-centered learning. Based on the results of problem identification and needs analysis, data was obtained that the teaching modules used so far have not been fully able to facilitate the in-depth development of students' competencies, especially in the aspects of critical thinking, problem solving, collaboration, creativity, and learning reflection. This research was carried out using one of the stages in the research and development method, namely the product design stage. Deep Learning-based teaching modules  are designed through preliminary studies which include analysis of teacher and student needs, analysis of student characteristics, curriculum analysis, and theoretical studies on deep learning. Based on the results of the study, a Deep Learning-based teaching module design was obtained  which consists of several main components, namely cover design, foreword, table of contents, general information of the module, learning outcomes and objectives, concept maps, learning activities that integrate mindful, meaningful, and joyful principles learning, student activity sheets, learning assessments, reflections, and bibliographies. The design of this teaching module is expected to support the creation of a more meaningful learning experience and improve the quality of the process and learning outcomes of students.